(untitled) (Journal of Surgical Sciences, 2020)
Background and Objective: Seroma is encountered as the commonest complication after mastectomy. Though various factors are suspected in causation of seroma, in this prospective study we tried to evaluate role of two different surgical technique of MRM in causation of seroma formation. Materials and Methods: In this observational comparative study, a total 90 patient of early breast carcinoma who had undergone Modified Radical Mastectomy (MRM) in 3 tertiary care hospitals of Dhaka were divided into 2 groups. In Group A, we used electrocautery for raising the skin flap and axillary dissection while in Group B we used curved Metzenbaum scissors to raise the skin flap along with aid of suture ligation for axillary dissection. Incidence of seroma formation was compared in both the groups. Results: Incidence of seroma was significantly higher with use of electrocautery. Results in both the groups were compared by Chi-square method, and statistically significant difference in incidence of seroma formation was found between two groups. Conclusion: Breast surgery, as MRM does not support injudicious use of electrocautery. Journal of Surgical Sciences (2019) Vol. 23(2): 87-89